2016
DOI: 10.1016/j.cmi.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological outcome in septic patients with extremely low 25-hydroxyvitamin D levels at initiation of critical care

Abstract: A relationship between vitamin D status and mortality in patients in intensive care units (ICU) has been documented. The present study aims to describe the clinical profile and sepsis-related outcome of critically ill septic patients with extremely low (<7 ng/mL) vitamin D levels at ICU admission. We conducted an observational study in the ICU of a teaching hospital including all patients admitted with severe sepsis/septic shock and undergoing 25-hydroxyvitamin D (25(OH)D) testing within the first 24 hours fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
(46 reference statements)
3
26
0
4
Order By: Relevance
“…Hipovitaminose D e mortalidade na terapia intensiva Dos trabalhos selecionados, 4 trataram diretamente da hipovitaminose D como preditora de mortalidade em pacientes críticos da faixa etária adulta, em situações em que não houve administração da vitamina nos grupos estudados. [11][12][13][14] Estudo de coorte realizado em UTI de hospital de ensino em Roma, na Itália, analisou todos os pacientes internados com sepse grave ou choque séptico que tiveram os seus níveis de 25OHD dosados nas primeiras 24 horas após admissão. Considerou-se como ponto de corte para deficiência de vitamina D valores séricos de 20 ng/ml, e níveis < 7 ng/ml como extremamente baixos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Hipovitaminose D e mortalidade na terapia intensiva Dos trabalhos selecionados, 4 trataram diretamente da hipovitaminose D como preditora de mortalidade em pacientes críticos da faixa etária adulta, em situações em que não houve administração da vitamina nos grupos estudados. [11][12][13][14] Estudo de coorte realizado em UTI de hospital de ensino em Roma, na Itália, analisou todos os pacientes internados com sepse grave ou choque séptico que tiveram os seus níveis de 25OHD dosados nas primeiras 24 horas após admissão. Considerou-se como ponto de corte para deficiência de vitamina D valores séricos de 20 ng/ml, e níveis < 7 ng/ml como extremamente baixos.…”
Section: Resultsunclassified
“…Os pacientes com níveis extremamente baixos apresentaram uma taxa de mortalidade relacionada à sepse significativamente maior do que o restante da amostra (50,9% versus 26%), além de uma duração mais longa de ventilação mecânica e de necessidade de suporte vasopressor, o que apontou que a hipovitaminose D grave pode ser um forte preditor de mortalidade relacionada à sepse. 11 Por sua vez, outro estudo italiano, realizado em Florença, comparou pacientes admitidos em UTI por duas diferentes causas: sepse grave/choque séptico (92 pacientes) e vítimas de trauma (72 pacientes). Ambos os grupos tiveram baixos níveis de vitamina D à admissão, com média de 10,1 ng/ml no grupo de pacientes sépticos e de 18,4 ng/ml em pacientes traumatizados, havendo diferença estatisticamente significativa entre os níveis de 25OHD de tais grupos.…”
Section: A Suplementação De Vitamina D No Paciente Críticounclassified
“…However, those with septic shock had significantly lower levels of 25(OH)D, which was closely related to higher CV-SOFA scores (r = −0.206, p < 0.001). Systematic analysis of the relationship between vitamin D and septic shock has not been previously conducted, though the earlier study found that septic shock patients with extremely low vitamin D levels needed vasopressor support for a more extended period (30). Another previous study also indicated that vitamin D deficiency affects the catecholamine system and exacerbates the instability of the cardiovascular system (31).…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of 25(OH)D are associated with increased overall mortality in the human population (Melamed, Michos, Post, & Astor, 2008), time of hospitalization (De Pascale et al, 2016;Higgins et al, 2012;Matthews, Ahmed, Wilson, Griggs, & Danner, 2012) and disease severity (Anwar et al, 2017). Meta-analysis studies have shown that serum concentrations of 25(OH)D may be independent predictors of survival in people with a wide variety of diseases (Schöttker et al, 2014), and the prevalence of lower vitamin D concentrations in critically ill people is about 82% (Melamed et al, 2008).…”
Section: Vitamin D As a Predictor Of Mortalitymentioning
confidence: 99%